Analisis Penataan Koridor Jalan Ahmad Yani Kota Bukittingi dengan Konsep Livable Street - HARDI, RESTY APRILA; Adewoso Tri Wijiono (Archvisual: Jurnal Arsitektur dan Perencanaan, 2026)
The Ahmad Yani Street corridor in Bukittinggi plays an important role in supporting economic activity, tourism, and urban mobility. However, the corridor's current state does not fully align with the principles of a livable street, particularly with regard to pedestrian comfort and accessibility. This study aims to analyze the quality of the Ahmad Yani Street corridor based on the livable street concept by identifying its physical conditions and users' perceptions. Field observations and questionnaires distributed to corridor users were used as research methods. The data were analyzed using a quantitative descriptive approach with a Likert scale. The analysis was based on three main variables: feasibility, accessibility, and comfort. The results show that accessibility received a high rating with an average score of 4.1, while feasibility and comfort received relatively low ratings with average scores of 2.9 each. The main problems identified include inadequate pedestrian paths, limited shading vegetation, and insufficient supporting facilities such as benches, trash bins, and guiding blocks for people with disabilities. Based on these findings, the Ahmad Yani Street corridor has not fully met the principles of a livable street, particularly in terms of comfort and feasibility. Recommended improvements include enhancing the pedestrian paths, providing additional shading vegetation, and offering supporting facilities and a more pedestrian-friendly street design. This study is expected to provide a basis for improving the quality of the corridor and creating more inclusive urban spaces in Bukittinggi.